A cross sectional study to assess the pattern of maternal mortality in a tertiary level government hospital of a city in north India - Lamba, Akanksha; Agarwal, Sakshi; Dutta, Apurba Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The index of the quality of health care delivery system of a country is reflected by its maternal mortality rate (MMR). Epidemiological data pertaining to maternal mortality is valuable in each set up to design interventional programs to favourably reduce the same. The objective of our study was to evaluate the maternal mortality rate in a tertiary care hospital, to assess the epidemiological aspects and causes of maternal mortality. Methods: A retrospective study of hospital records and death summaries of all maternal deaths over the period from January 2010 to December 2012 was carried out. Maternal mortality rate, epidemiological factors and causes affecting maternal mortality were assessed. Results: A total of 45 maternal deaths occurred per 7,266 live births out of which unbooked and late referrals accounted for 75.55 % of maternal deaths. Most maternal deaths occurred in the age group of 20–30 years, multiparous women (73.33%) and women from rural areas (71.11%). Direct obstetric causes accounted for 82.22% of maternal deaths where as 15.55% of maternal deaths were due to indirect causes. Maternal mortality rate (MMR) came out to be 627.79 per 100,000 live births. Hemorrhage was the commonest cause of death (37.33 %), followed by pregnancy-induced hypertension including eclampsia (15.55 %) and sepsis (11.11%). Conclusions: Hemorrhage, sepsis, and pregnancy-induced hypertension including eclampsia were found to be the direct major causes of death. There is a wide scope for improvement as a large proportion of the observed deaths are preventable.